Beuchot’s formal analogism within Peter Singer’s philosophy - Barrientos-Rastrojo, José (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This paper analyses an analogic reading of singerian ethics. Firstly, it studies Mauricio Beuchot’s analogical hermeneutics grounds. Then, it takes them to each of the Peter Singer’s ethical universes. Finally, it reveals the scheme of his ethic that will be followed in his future works. Therefore, this article has a prospective mission related to Professor Singer and it has an practical mission related to Mauricio Beuchot because it determines a practical performance to his analogical hermeneutics.
Keywords: consequentialism; utilitarianism; analogy; hermeneutics